Measurement of surface dose in an MR‐Linac with optically stimulated luminescence dosimeters for IMRT beam geometries. Issue 7 (27th May 2020) - Lim‐Reinders, Stephanie; Keller, Brian M.; Sahgal, Arjun; Chugh, Brige; Kim, Anthony
Abstract : Purpose: This study aims to measure the surface dose on an anthropomorphic phantom for intensity‐modulated radiation therapy (IMRT) plans treated in a 1.5 T magnetic resonance (MR)‐Linac. Previous studies have used Monte Carlo programs to simulate surface dose and have recognized high surface dose as a potential limiting factor for the MR‐Linac; however, to our knowledge surface dose measurement for clinical plans has not yet been published. Given the novelty of the MR‐Linac, it is important to perform in vivo measurements of a potentially dose‐limiting factor such as surface dose when moving forward for clinical use. Methods: Optically stimulated luminescence dosimeters (OSLDs) were used on an anthropomorphic phantom. Intensity‐modulated radiation therapy plans were generated to treat a near‐surface breast tumor in the phantom. The tumor was treated with 2, 3, 5, 7, and 9 beam IMRT plans with a 1.5 T MR‐Linac using a 7‐MV photon beam. The plans were generated in a Monte Carlo treatment planning system (TPS) capable of modeling magnetic field effects. The surface dose was sampled in seven locations on the surface surrounding the planning target volume (PTV), and in two different OSLD configurations with the dosimeters measuring water equivalent depths of 0.16 and 0.64 mm. The TPS was used to estimate the doses at the OSLD locations. In addition, MR images were taken of a pork belly with and without an OSLD placed anteriorly placed to determine the effect of an OSLD on image fidelity. Results: For the 3, 5, 7, and 9‐beam configurations, surface doses were approximately half that of the prescription dose to the simulated tumor, although the magnitude of the skin dose relative to the prescription is certainly also dependent on individual patient anatomy. The general trend for both TPS and measurements was that the greater the number of beams, the lower the skin doses and dose readings; also, with increasing numbers of beams, doses at shallow depths become lower relative to deeper depths. The MR images showed that the presence of the OSLD did not induce clinically relevant geometric distortions or intensity differences. Conclusions: To our knowledge, this study is the first of its kind to experimentally measure the surface dose in an MR‐Linac for IMRT plans. This study has explored the use of OSLDs to measure in vivo surface dose in a clinical setting. OSLDs may be used to measure skin dose clinically when there are concerns of skin radiation burns and near‐surface toxicity. Optically stimulated luminescence dosimeters are promising devices for in vivo surface dosimetry in an MR‐Linac.